NON FUNGIBLE TOKEN SEBAGAI ASET DIGITAL DALAM PANDANGAN FIQH MUAMALAH - Robbani, Shofa; Khoiria Ningrum, Ifa (At-Tuhfah : Jurnal Studi Keislaman, 2022)
The phenomenon of buying and selling online continues to grow, especially in 2022, when Ghozali shocked the Indonesian people by selling 933 non-fungible token digital works for $1.5 billion on the OpenSea Online Market. But not all people respond, because everyone can sell other people's art, sell images that contain pornography, and commit fraud under the guise of investment. In Sharia economic law, on the other hand, the element of fraud and the sale of something that does not belong to him are prohibited. The mechanism of buying and selling non-fungible tokens on the OpenSea online market is discussed in this study, as well as how the law is based on Islamic economics.This type of research uses a qualitative approach by seeking direct data from parties involved in buying and selling non-fungible tokens on the Opensea online marketplaces, from journals, articles, books, and other sources. The theory of "al-mal" and "al-bai' is used to analyze this research using a qualitative deductive method. The results of the research show three mechanisms in the practice of buying and selling non-fungible tokens on the Opensea online marketplace, which include the creation, sale, and purchase of digital artwork, and most of them are carried out on the Ethereum and Polygon blockchain platforms. According to sharia economic law, when buying and selling non-fungible tokens on the Opensea online market is analyzed using the mall theory, the majority of Ulama argue that non-fungible tokens can be classified as malls, while some groups of followers of Imam Hanafi do not justify non-fungible tokens as malls because of their non-concrete nature. Meanwhile, if it is captured using the "bai' theory, the practice of buying and selling non-fungible tokens is not covered by sharia because, in practice, people can easily sell other people's digital artwork, sell images that contain pornographic elements, and are very vulnerable to involvement in non-fungible token sale scams such as forgery of digital artwork descriptions and investment scams. As for those who can avoid all these negative elements, then they are returned to the original law of bai', namely mubah.